Current Understanding of Osteoimmunology in Certain Osteoimmune Diseases - Zhou, Anqi; Wu, Bingfeng; Yu, Hui; Tang, Yufei; Liu, Jiayi; Jia, Yinan; Yang, Xiaoyu; Xiang, Lin (Frontiers in Cell and Developmental Biology, 2021)
The skeletal system and immune system seem to be two independent systems. However, there in fact are extensive and multiple crosstalk between them. The concept of osteoimmunology was created to describe those interdisciplinary events, but it has been constantly updated overtime. In this review, we summarize the interactions between skeletal and immune system in the co-development of the two systems and the progress of certain typical bone abnormalities and bone regeneration on the cellular and molecular levels according to the mainstream novel study. At the end of the review, we also highlighted the possibility of extending the research scope of osteoimmunology to other systemic diseases. In conclusion, we propose that osteoimmunology is a promising perspective to uncover the mechanism of related diseases, meanwhile, study from the point of view of osteoimmunology may also provide innovative ideas and resolutions to achieve the balance of internal homeostasis.